Photography in India. From Archives to Contemporary Practice. - Blaney, Aileen; Fox, Anna; Raqs Media Collective; Shah, Chinar; Wilson, Denise, A. (Londen : Bloomsburry, 2018)
Pinckers, Max ; Bhaskar, Binu ; Gill, Gauri ; Vangad, Rajesh ; Shiva, Cop ; Channa, Imran ; Punjabi, Suresh ; HG, Arunkumar ; Katragadda, Harikrishna ; Sinha, Aniruddha ; Rahman, Ram ; Charuau, Fabien ; Kessels, Erik ; Culmann, Olivier ; Waswo, Waswo X.
Indian Photography, contemporary photography
boek